Pengembangan Kawasan Perdesaan Berbasis Tanaman Pangan di Kecamatan Amuntai Utara Kabupaten Hulu Sungai Utara - Faisal Azmi; Azwar Saihani; Heldawati Heldawati (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2019)
This study aims to determine (i) the comparative advantage of food crop commodities and food crop base sectors, (ii) competitive advantages of food crops and competitive and non-competitive areas, (ii) strengths, weaknesses, opportunities, and threats of rural food-based rural development in Amuntai Utara District, Hulu Sungai Utara Regency. The study was conducted on November 2018 - January 2019 in Amuntai Utara District Hulu Sungai Utara Regency with the research method used was descriptive qualitative and quantitative methods. Based on the results of the study, the LQ value in the North Amuntai Subdistrict has a base sector and non-base sector in food crop commodities; shift-share analysis shows that competitive commodities of rice food plants with a value of 0.12 and corn with a value of 0.56; SWOT analysis was obtained from an analysis of internal factors (IFAS) of 2,832 and external factor analysis (EFAS) of 2,45, hence the development of rural areas based on food crops was in quadrant I (supporting aggressive strategies)